2018
DOI: 10.1103/physrevb.98.104512
|View full text |Cite
|
Sign up to set email alerts
|

Spin-split conductance and subgap peak in ferromagnet/superconductor spin valve heterostructures

Abstract: We consider the separate spin channel contributions to the charge conductance in superconducting/ferromagnetic spin valve F 1 /N/F 2 /S structures. We find that the up-and down-spin conductance contributions may have a very different behavior in the subgap bias region (i.e. there is a spin-split conductance). This leads to a subgap peak in the total conductance. This peak behavior, which can be prominent also in N/F/S systems, is strongly dependent, in a periodic way, on the thickness of the intermediate ferro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In most of the earlier works on tunnelling spectroscopy [97][98][99][100][101][102][103][104][105][106][107][108][109], it was found that the barrier thickness play a very significant role on the transport mechanism. However, the role of barrier thickness on spin transport is yet to be understood.…”
Section: A Spin Conductance Spectra At the F|ncsc Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…In most of the earlier works on tunnelling spectroscopy [97][98][99][100][101][102][103][104][105][106][107][108][109], it was found that the barrier thickness play a very significant role on the transport mechanism. However, the role of barrier thickness on spin transport is yet to be understood.…”
Section: A Spin Conductance Spectra At the F|ncsc Interfacementioning
confidence: 99%
“…Transport properties in several F|Singlet SC [97][98][99], F|Triplet SC [100][101][102][103][104][105] and F|NCSC [106][107][108][109] heterostructures had been studied earlier. However, the role of magnetization in spin transport, spin current [110][111][112][113][114][115] and its interplay with pair potential, magnetic field and RSOC of NCSC in F|NCSC|F SV is still need to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the improvement and optimization of SSVs still remains both a theoretical and experimental challenge [32][33][34][35][36][37][38]. The possible ways to improve the SSV properties call for the optimization of the structures, via their technology of preparation, quality of interfaces, and choice of materials, including strong, half-metallic, and insulating ferromagnets.…”
Section: Introductionmentioning
confidence: 99%
“…Generalizing the well-established Blonder-Tinkham-Klapwijk model [59] to spin-valve junctions [60][61][62], we evaluate the junctions' zero-temperature tunneling conductance and elaborate on transport ramifications of unconventional Andreev reflections, predicting the formation of conductance double peaks close to the singlet-gap energy as a consequence of the effectively induced nonzero triplet gap. After demonstrating the expected huge magnetosensitivity of the double-peak conductance structure, we compute typical (T)MR ratios [63] and identify marked MR magnetoanisotropies, which provide another clear fingerprint of unconventional Andreev reflections.…”
Section: Introductionmentioning
confidence: 99%